Electrophysiological correlates of active suppression and attentional selection in preview visual search. (November 2018) - Berggren, Nick; Eimer, Martin
Abstract: Advance preview of a subset of distractor objects improves the efficiency of visual search performance, but the causes and mechanisms of such preview benefits remain unclear. Here, we employed event-related potential (ERP) markers of the selective processing of preview displays and full search displays in lateralised preview search tasks where only one side of the search displays was task-relevant. Preview displays elicited a sustained positivity contralateral to the relevant side (PD component), indicative of the active suppression of distractor objects on this side. Lateralised ERP components to full search displays revealed qualitative differences between attentional selection processes on preview as compared to no-preview trials. When search displays were preceded by preview displays, attention was directly allocated to target objects, while distractors remained unattended. When all search display objects were presented simultaneously (no-preview), attention was directed non-selectively to objects on the task-relevant side, even when no target was present. These results suggest that behavioural preview effects in visual search can be accounted for by the inhibition of previewed distractors, and the subsequent rapid attentional selection of target objects on preview trials. Highlights: Previewing irrelevant distractors improves subsequent visual search. We assessed mechanisms of preview search with event-related potentials. Previewed items elicited a lateralized positivity, linked to distractor suppression. Preview facilitated the rapid allocation of attention to subsequent targets. Findings support an inhibition model of preview benefits in visual search.